Analisis Komunikasi Keamanan: Perubahan Budaya Dalam Politik Generasi Z - Prasojo Prasojo (Jurnal Kajian Ilmiah, 2026)
The intersection between security communications and the evolving political landscape of Generation Z creates a complex field of study, requiring a deep understanding of cultural shifts, technological advances, and the unique socio-political awareness of this demographic group. Generation Z, often described as the digital generation, exhibits different patterns of information consumption, communication, and political engagement compared to previous generations. The pervasive influence of social media, increasing reliance on digital platforms for political information, and scepticism towards conventional institutions shape how Gen Z views and responds to security-related messages. Understanding these dynamics is crucial for rethinking security communication in a way that aligns with Gen Z's values, addresses their specific concerns, and encourages informed decision-making in an era of unprecedented digital connectivity and evolving security threats.